Advances in the measurement of intangible capital : papers from the 4th NYU Intangibles Conference - Chatzkel, Jay L. (Journal of intellectual capital ;, 2002)
This special conference issue of the Journal of Intellectual Capital focuses onpresentations given at the 4th NYU Research Conference on Intangibles held atthe New York University's Stern School of Business in April 2001. The Conference brought together researchers and practitioners who havetackled the central issues concerning intangibles: measurement and valuation.